PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA GIANT DEPT STORE CABANG BSD TANGERANG - Denok Sunarsi (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
This study aims to determine the effect of marketing mix and service quality on consumer satisfaction at Giant Dept Store BSD Tangerang Branch. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study marketing mix significantly influence consumer satisfaction by 37.7%, hypothesis testing obtained t count t table or (7.707 1.984). Service quality has a significant effect on customer satisfaction by 46.1%, the hypothesis test is obtained t count t table or (9,153 1,984). Marketing mix and service quality simultaneously have a significant effect on customer satisfaction with the regression equation Y = 9,780 + 0,293X1 + 0,476X2 and the contribution of effect is 53,8%, the hypothesis test is obtained F count F table or (56,404 2,700).